Auditor Ethics, Auditor Competence, and Audit Risk: The Mediating Role of Audit Fees on Audit Quality among Auditors in Public Accounting Firms in Surabaya - Nada Salsabila, Sausan; Tri Ratnawati (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2025)
This study aims to examine and analyze the influence of auditor ethics, auditor competence, and audit risk on audit quality, with audit fees serving as a mediating variable. This research employs a quantitative associative approach with a casual explanatory design. Data were collected through a questionnaire survey administered to external auditors working at Public Accounting Firms (PAFs) in Surabaya, with a population of 55 firms. The sampling technique used was convenience sampling, resulting in 42 auditors as respondents with the characteristic of having worked at Public Accounting Firms in Surabaya for at least one year as of 2025. Data analysis was conducted using the Partial Least Square (PLS) method assisted by SmartPLS 4.0 software. The results indicate that auditor competence and audit risk have a positive and significant effect on audit fees, while auditor ethics does not have a significant effect. Furthermore, auditor ethics has a positive and significant effect on audit quality, whereas auditor competence, audit risk, and audit fees do not show a significant effect. In addition, audit fees are not proven to function as a mediating variable and therefore are unable to mediate the effects of auditor ethics, auditor competence, and audit risk on audit quality.